Pengaruh Good Corporate Governance dan Kebijakan Hutang terhadap Manajemen Laba dengan Kinerja Keuangan sebagai Pemoderasi - Soeparyono, Regina Deia (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This research aims to analyze the impact of good corporate governance and debt policy on earnings management practices, with financial performance as a moderator. The research method applied is an associative quantitative approach using secondary data. The population considered consists of non-cyclical companies listed on the Indonesia Stock Exchange during the period 2018-2022, totaling 113 companies. Samples were selected using purposive sampling method, with four specific criteria resulting in 32 companies as samples, yielding a total of 160 data observations. Data analysis was conducted through descriptive statistical techniques, panel data regression model estimation, classical assumption tests, hypothesis testing, and Moderated Regression Analysis (MRA) using Eviews 10 software. The research findings indicate that good corporate governance measured by the Board of Directors proxy partially significantly influences earnings management practices. However, the influence of good corporate governance measured by the Independent Commissioners proxy is not statistically significant on earnings management practices. Furthermore, debt policy also does not significantly affect earnings management practices. Additionally, it was found that financial performance does not moderate the relationship between the Board of Directors and Independent Commissioners with earnings management practices, nor does it moderate the relationship between debt policy and earnings management practices.